What Do 50 Years of Census Records and Household Survey Data Tell Us about Human Opportunities and Welfare in Latin America? - Calvo-Gonzalez, Oscar; Caruso, German D.; Castaneda-Aguilar, R. Andres; Malasquez, Eduardo A. (World Bank, Washington, DC, 2020)
To comprehend how development really happens, it is necessary to understand the evolution of its drivers and their relationship with individuals' income. This paper analyzes the expansion of access to education and basic services in Latin America and its association with the evolution of incomes in the region. The paper focuses on the importance of access to opportunities as one of the drivers of development and highlights the role of policy making. The findings suggest that access to education and basic public services early in life are positively correlated with incomes in adulthood. The analysis also suggests that countries follow a dissimilar path to increase access to education and basic services. The paper undertakes a comprehensive analysis of historic census records to add granularity to the assessment of the development of countries, matched with detailed individual-level information from household surveys of several countries in the region. The paper widens an ongoing area of research on the long-run relationship between access to opportunities during childhood and incomes in adulthood.